2020
DOI: 10.3390/ani10091499
|View full text |Cite
|
Sign up to set email alerts
|

Overfeeding-Induced Obesity Could Cause Potential Immuno-Physiological Disorders in Rainbow Trout (Oncorhynchus mykiss)

Abstract: Although over-nutrition from overfeeding-induced obesity is known to be highly associated with metabolic and immunological disorders in humans, little is known about overfeeding-induced obesity in fish farming. The purpose of this study was to investigate changes in immuno-physiological parameters, to better understand the potential risk of overfeeding–induced obesity in fish. Commercial feed was provided to fish in the overfed group until they refuse to eat, but fish in the control group was fed with the feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 63 publications
0
9
0
2
Order By: Relevance
“…On the contrary, it has been observed that short term overfeeding of zebrafish with a high fat diet led to metabolic alterations, such as hyperglycemia and ectopic lipid accumulation in the liver [ 77 ]. Another study on overfeeding in rainbow trout observed the development of immunological disorders and increased susceptibility to infectious diseases [ 78 ]. In aquaculture, fish with better immunity and health would be preferred, as they would be more resistant to disease outbreaks, protecting the farmers from substantial loss.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it has been observed that short term overfeeding of zebrafish with a high fat diet led to metabolic alterations, such as hyperglycemia and ectopic lipid accumulation in the liver [ 77 ]. Another study on overfeeding in rainbow trout observed the development of immunological disorders and increased susceptibility to infectious diseases [ 78 ]. In aquaculture, fish with better immunity and health would be preferred, as they would be more resistant to disease outbreaks, protecting the farmers from substantial loss.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, over-feeding (as a possible result of strong dominance hierarchies, incomplete training of personnel, etc. ), though less studied, may have welfare consequences such as fouling of the holding tank or net-pen and/or obesity resulting in possible immunological disorders (131).…”
Section: Feed Quality and Managementmentioning
confidence: 99%
“…Intestinal pathological problems resulting from experimental fish diets reflecting an obstacle in the replacement of fish proteins with alternative sources have frequently been reported [27,28,38,41,51]. Intestinal health is crucial for animal growth and the efficiency of animal feeds [52][53][54]. Intestinal pathological problems in farmed fish can be associated with the disruption of intestinal function and reduction in the efficiency of feed conversion [37].…”
Section: Probiotics Can Reduce Subacute Intestinal Pathological Problems Improve Feed Conversion and Reduce Disease Outbreaks Mortality Amentioning
confidence: 99%
“…Intestinal pathological problems in farmed fish can be associated with the disruption of intestinal function and reduction in the efficiency of feed conversion [37]. Subacute intestinal pathological problems, such as sub-acute intestinal inflammation [54], can affect feed digestibility [52]. Intestinal pathological issues may affect normal intestinal functions and produce a higher intestinal pathological index score; the subsequent inflammation can therefore result in higher excretion of nutrients resulting from impaired digestion [52][53][54].…”
Section: Probiotics Can Reduce Subacute Intestinal Pathological Problems Improve Feed Conversion and Reduce Disease Outbreaks Mortality Amentioning
confidence: 99%